Complexity in large-scale technical project management. (1st January 2011) - Sheard, Sarah; Mostashari, Ali
Complexity is a catch-all term that is used to express many different factors that cause problems in the management of projects. This paper presents a framework for systematising the description of different types and measures of complexity. First, the attributes that appear in different definitions and uses of the word complexity are compared. Some are shown to be causes of system and project complexity, and some are shown to be effects. Next, types of complexity from previous work are explained. Finally, those types of complexity are applied to different aspects of a large-scale technical development projects: the project building a technological system, that system itself, the environment into which the system will be inserted, and, to some extent, the interpretation of these factors as being 'complex' or not by the humans involved in the system.